Զակամ գավառը Ժէ դ.-ԺԸ դ. առաջին քառորդին - Եսայան, Անդրանիկ (Մատենադարան)
After the Persian-Ottoman sustained wars, from the second decade of 17th century, favorable conditions for demographic growth emerged in the Zakam province (currently, the territory of the province is part of the Getabek, Shamkor and Tovuz regions of the Republic of Azerbaijan). Construction works and activity in the spiritual life can be mentioned. As a result, Armenians from other places settled here, the old settlement was expanded, and new villages were founded. But the weakening of the Safavid Empire in the latter part of the century and the frequent Lezgin invasions led to grave consequences. Some villages were destroyed, and a part of the population was taken captive. The Ottoman Empire, in agreement with the Russian side, occupied the entire region in 1725. The Extensive Register of the Gandja- Karabakh Provinces submitted in 1727 by the Turks contains important information on the demographic and economic situation in Zakam. The study of its data demonstrates that despite the unfavorable conditions and the recent wars, the province Zakam preserved numerous Armenian population which formed an absolute majority. Созданные в 17 в. благоприятные условия положительно сказались с точки зрения прироста населения провинции Закам (в настояшее время территории провинции входят в состав Гетабегского, Шамкорского и Товузского районов Республики Азербайджан). В провинции проводились строительные работы, активизировалась духовная жизнь. Здесь нашли убежище также армяне из других местностей. Старые поселения постепенно расширялись, основывались новые деревни. Однако ослабление в конце века империи Сефевидов и неоднократные нашествия лезгинов привели к тяжелым последствиям. Ряд деревень были разрушены, часть населения взята в плен. За этим последовала оккупация региона Османской империей. «Пространный реестр Гянджа-Карабахской провинции» составленный в 1727 г. турками, содержит важную информацию по ряду вопросов, касающихся демографии и экономики провинции Закам. Изучение данных показывает, что, несмотря на то что провинция сильно пострадала, там, тем не менее сохранилось многочисленное армянское население, составлявшее абсолютное большинство․
Keywords: Պատմություն